The correlation between earphone usage patterns with the incidence rate and severity of tinnitus - Adrian Joshua Velaro; Devira Zahara (Oto Rhino Laryngologica Indonesiana, 2021)
ABSTRACTBackground: Earphone nowadays is extensively used along with audiovisual technology development. The increased use of earphone can lead to tinnitus. Around 10- 20% of the adult population had experienced tinnitus during their life, and 0.5-2.5% affected their quality of life. Tinnitus in medical students could interfere in the teaching process which could can lead to decreased quality of medical students. Objective: To observe the correlation between the pattern of using earphone with the incidence of tinnitus, and to determine the severity of tinnitus among students of the Faculty of Medicine, Universitas Sumatera Utara, class 2017-2019 who used earphones. Method: This was an analytic study with cross-sectional design, using consecutive sampling technique. Result: Bivariate analysis between earphone use patterns and the incidence of tinnitus among the subjects obtained statistically significant results (p=0.017). Univariate analysis on 148 respondents showed a pattern of risky earphone use (64.2%) and 52 people with tinnitus (35.1%), and tinnitus severity with 52 participants based on Visual Analogue Scale was mild (55.8%) and based on Tinnitus Handicap Inventory Questionnaire was light (53.9%). In the pattern of earphone use, the results of the analysis of the frequency of using earphones for 3-4 days were (40.5%), the volume of earphone use was 60-80% (54.1%), the length of time using earphones >3 years was (65.5%), and the duration of using earphones <1 hour (38.5%). Conclusion: There was a correlation between the pattern of earphone use and the incidence of tinnitus among students at the Faculty of Medicine, Universitas Sumatera Utara, class 2017-2019.Keywords: earphone, tinnitus, Visual Analog Scale, Tinnitus Handicap Inventory QuestionnaireABSTRAKLatar belakang: Earphone saat ini sangat banyak digunakan seiring dengan perkembangan teknologi audiovisual. Prevalensi pengguna earphone pada remaja sekitar 83,6% dari 436 remaja. Penggunaan earphone yang berlebihan dapat menyebabkan tinitus. Statistik prevalensi dunia menunjukkan 30-40% populasi dewasa pernah mengalami tinnitus dalam hidupnya dan 0,5-2,5% kualitas hidupnya sangat terganggu oleh tinitus. Tinitus merupakan salah satu tanda penurunan fungsi pendengaran dan mampu menyebabkan penurunan performa kognitif. Tinitus pada mahasiswa kedokteran dapat mengganggu proses belajar mengajar sehingga dapat menurunkan kualitas mahasiswa kedokteran. Tujuan: Untuk mengetahui apakah terdapat hubungan pola penggunaan earphone dengan angka kejadian tinnitus serta tingkat keparahan tinitus pada mahasiswa Fakultas Kedokteran Universitas Sumatera Utara. Metode: Penelitian analitik dengan desain potong lintang dengan teknik pengambilan secara consecutive sampling. Pengukuran dilakukan dengan Visual Analog Scale (VAS) dan Tinitus Handicap Inventory Questionnaire (THI-Q). Hasil: Analisis bivariat antara pola penggunaan earphone dengan angka kejadian tinnitus pada mahasiswa Fakultas Kedokteran Universitas Sumatera Utara diperoleh hasil (p=0,017). Analisis univariat pada 148 responden menunjukkan pola penggunaan earphone berisiko sebanyak (64,2%) dan yang mengidap tinitus sebanyak 52 orang (35,1%), dan tingkat keparahan tinitus dengan jumlah responden 52 orang berdasarkan VAS adalah ringan (55,8%) dan berdasarkan THI-Q adalah ringan (53,9%). Pada pola penggunaan earphone diperoleh hasil analisis frekuensi penggunaan earphone 3-4 hari sebanyak (40,5%), volume penggunaan earphone 60-80% sebanyak (54,1%), lama penggunaan earphone >3 tahun sebanyak (65,5%), dan durasi penggunaan earphone <1 jam sebanyak (38,5%). Kesimpulan: Terdapat hubungan antara pola penggunaan earphone dengan angka kejadian tinitus pada mahasiswa Fakultas Kedokteran Universitas Sumatera Utara angkatan 2017-2019.Kata kunci: earphone, tinitus, Visual Analog Scale, Tinnitus Handicap Inventory Questionnaire